Hiring Practices in Private Practice Interventional Radiology - Mustert, Bryan (Seminars in Interventional Radiology, 2019)
The growth of interventional radiology over the last several decades has changed the specialty into a dynamic, clinically based practice, vital to the function of a successful radiologic practice. This growth of the specialty has been paralleled by our own sections growth in a large Midwest private practice radiology group. This article looks at our experience in hiring interventional radiologists, including evaluation of our process, successes, and failures, along with lessons learned.
Keywords: interventional radiology; hiring; interview; private practice